2003
DOI: 10.1073/pnas.2334537100
|View full text |Cite
|
Sign up to set email alerts
|

The glycine neurotransmitter transporter GLYT1 is an organic osmolyte transporter regulating cell volume in cleavage-stage embryos

Abstract: Cells subjected to sustained high osmolarity almost universally respond by accumulating compatible organic osmolytes that, in contrast to inorganic ions, are not deleterious even at high intracellular concentrations. Their accumulation from the external environment by known organic osmolyte transporters, such as the four identified in mammals, occurs only slowly in response to sustained high osmolarity, by synthesis of new transporter proteins. Most cells, however, are not subject to high or varying osmolarity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
145
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 100 publications
(167 citation statements)
references
References 33 publications
13
145
0
Order By: Relevance
“…This was demonstrated directly using 3 H-glycine, showing that glycine was indeed accumulated by 1-and 2-cell mouse embryos and that the steady-state level of intracellular glycine varied proportionally with the osmolarity of the external medium (Dawson et al, 1998;Steeves et al, 2003). Such linear dependence of intracellular glycine content on external osmolarity was precisely the relationship expected if the accumulated intracellular glycine is balancing external osmolarity.…”
Section: Organic Osmolyte Usage By Preimplantation Embryosmentioning
confidence: 65%
See 4 more Smart Citations
“…This was demonstrated directly using 3 H-glycine, showing that glycine was indeed accumulated by 1-and 2-cell mouse embryos and that the steady-state level of intracellular glycine varied proportionally with the osmolarity of the external medium (Dawson et al, 1998;Steeves et al, 2003). Such linear dependence of intracellular glycine content on external osmolarity was precisely the relationship expected if the accumulated intracellular glycine is balancing external osmolarity.…”
Section: Organic Osmolyte Usage By Preimplantation Embryosmentioning
confidence: 65%
“…Baltz, unpublished). A highly selective GLYT1 inhibitor, ORG23798, blocked virtually all glycine transport by cleavage stage embryos (Steeves et al, 2003;Tartia et al, 2009), confirming that glycine transport is overwhelmingly via GLYT1 in preimplantation mouse embryos prior to compaction. Glycine transport via GLYT1 is also present in human embryos (Hammer et al, 2000), implying a similar role there, although this remains to be confirmed.…”
Section: Glycine Transport and Accumulation By Embryosmentioning
confidence: 80%
See 3 more Smart Citations